THE IMPLEMENTATION OF A CARBON TAX WITHIN THE INDONESIAN TAX LEGAL SYSTEM: A LITERATURE REVIEW FOLLOWING THE ENACTMENT OF THE HPP ACT - Gunawan Widjaja (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This study examines the implementation of carbon tax within the Indonesian tax law system following the Tax Regulation Harmonisation Act. Carbon tax serves as a fiscal instrument that not only functions to increase state revenue but also to control greenhouse gas emissions through the internalisation of external costs arising from carbon-emitting activities. This study employs a literature review using a normative legal approach to examine the legal framework of the carbon tax, the challenges to its implementation, and its prospects in supporting the transition towards low-carbon development. The findings indicate that the HPP Act has provided an important initial legal foundation; however, the implementation of the carbon tax still faces obstacles in the form of unclear technical standards, institutional readiness, inter-sectoral coordination, and potential economic and social impacts. On the other hand, a carbon tax holds great promise as an environmental policy instrument if supported by clear secondary legislation, a robust monitoring system, and fair compensation mechanisms. Thus, a carbon tax has the potential to become an important part of tax reform aligned with Indonesia’s sustainable development goals.